Development of a Project-Based Learning Model Using Science Games to Enhance Social Skills in Early Childhood - Khairul Huda; Sofia Hartati; Ade Dwi Utami (Journal of Educational Studies, 2026)
Social skills in early childhood are the primary foundation for future success, as through these skills children learn to build relationships, cooperate, understand others’ feelings, and adapt to increasingly complex social environments. However, in early childhood education (PAUD) practices, the development of social skills is often not optimally facilitated through enjoyable and meaningful activities. This study aims to develop a Project-Based Science Play Learning Model (ProperSains) to enhance the social skills of young children. The study employed a Research and Development (R&D) approach following the Borg and Gall framework. The research sample consisted of 73 children aged 5–6 years, selected using a purposive sampling technique, including 9 children in the limited trial, 32 children in the large-scale trial, and 32 children in the operational field trial. The research instruments included questionnaires, social skills assessment sheets, and model implementation observation sheets. Data were analyzed using both qualitative and quantitative techniques. The results indicated that: (1) the preliminary study revealed that most teachers had not yet fully understood or implemented the project-based science play learning model; nevertheless, the majority of teachers expressed the need for its application in early childhood education institutions in East Lombok Regency; (2) the ProperSains learning model was successfully developed through the systematic stages of Research and Development (R&D) based on the Borg and Gall framework; (3) the developed ProperSains model was proven to be feasible and practical in improving the social skills of children aged 5–6 years; and (4) the ProperSains model was effective in enhancing early childhood social skills, particularly in aspects of cooperation, communication, sharing, participation, and adaptation. In conclusion, the ProperSains model is a valid, practical, and effective learning model for fostering social skills among children aged 5–6 years. These findings suggest that the model has the potential to be implemented in early childhood education settings with similar characteristics, making it a promising alternative pedagogical approach for promoting children's social development through project-based science play activities. Further studies involving broader geographical contexts and more diverse participant characteristics are recommended to strengthen the generalizability of the findings.